Development and implementation of the FTA-FMEA6 methodology for process improvement in manufacturing - Lira, Silas Almeida; Duarte, Armando Dias; Barros, Adriano David Monteiro de; Costa, Jefferson Carlos de Oliveira Ribeiro (Brazilian Journal of Production Engineering, 2023)
This study presents the results of the methodology developed through the integration of Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) tools, referred to as FTA-FMEA6. The aim was to reduce variation and enhance stability in the gravity casting process of metal inserts in a subsection dedicated to electrical accumulators of a multinational automotive company located in Belo Jardim, PE. After applying the proposed methodology, 21 improvement opportunities were identified, and subsequent actions were implemented, resulting in equipment and process modifications. The process capability indicators demonstrated a significant change for the organization through the reduction of process variation and instability.